Monitoring drug trends in the digital environment-New methods, challenges and the opportunities provided by automated approaches - Guarita, Bruno; Belackova, Vendula; van der Gouwe, Daan; Blankers, Matthijs; Pazitny, Martin; Griffiths, Paul (The International journal on drug policy, 2021)
Developments in information technology have impacted on all areas of modern life and in particular facilitated the growth of globalisation in commerce and communication. Within the drugs area this means that both drugs discourse and drug markets have become increasingly digitally enabled. In response to this, new methods are being developed that attempt to research and monitor the digital environment. In this commentary we present three case studies of innovative approaches and related challenges to software-automated data mining of the digital environment: (i) an e-shop finder to detect e-shops offering new psychoactive substances, (ii) scraping of forum data from online discussion boards, (iii) automated sentiment analysis of discussions in online discussion boards. We conclude that the work presented brings opportunities in terms of leveraging data for developing a more timely and granular understanding of the various aspects of drug-use phenomena in the digital environment. In particular, combining the number of e-shops, discussion posts, and sentiments regarding particular substances could be used for ad hoc risk assessments as well as longitudinal drug monitoring and indicate "online popularity". The main challenges of digital data mining involve data representativity and ethical considerations.
Keywords: Online surveillance; monitorování léčiv; E-shops; obchod; Natural language processing; Text mining; Commerce; Psychoactive substances; data mining; Substance-Related Disorders; léčivé přípravky; Drug Monitoring; poruchy spojené s užíváním psychoaktivních látek; Humans; Data mining; Pharmaceutical Preparations; Data Mining; Internet-based drug forums; lidé